Species’ variety of ephitipical lichens as an indicational sign of humain influence on forest ecosistems of steppe zone - V. V. Zasoba; E. U. Medenez (Юг России: экология, развитие, 2015)
Species’ variety of ephitipical lichens in different kinds of man-made plants of forests’ ecosistems in steppe zone of south Russia is represented at the article. The dinamic of appearence of ephitipical lichens at the different stadies of forest’s development was watched. On the base on found speciesindificators the works were held in Novocherkassk, Rostov district.